(untitled) (Agroindustria, Sociedad y Ambiente, 2023)
Technological tools are being used in the teaching of distance academic programs, especially in careers in the area of agronomy and agroindustrial where practical activities are limited by the difficulty of access to processing centers, as well as budgetary restrictions that They affect the provision of laboratories, a situation that worsened due to the measures that were taken with the arrival of COVID-19, which would also allow students from foreign areas or in poverty to be included. However, in addition to the technical limitations for the use of ICT, teachers express the difficulty of teaching subjects that include practical activities such as those required in the training of agronomy and agro-industrial engineers, which are still based on a behavioral model with a unidirectional flow of information, for which it is necessary to carry out an intervention in order to make a methodological proposal that contributes to the use of information technology tools (ICT) that promote the integration of the different competences of professionals of agriculture and agro-industry, having as premises the improvement of technological infrastructure and internet access, an interdisciplinary and transdisciplinary vision of the process through the participatory action of students and teachers, whose goal is to increase the number of subjects online, student pursuit, admission rate and problem solving in the context of the Dean of Agronomy through academic projects mediated by ICTs.